PENYELESAIAN MASALAH PEMBONCENGAN REPUTASI TERHADAP MEREK TERKENAL MENURUT TEORI FRIEDMAN - Nidzom Muhib; Elfrida Ratnawati Gultom (Ensiklopedia of Journal, 2023)
There are still many violations against trademark, especially against well-known trademark. Trademark is a sign that is used as a differentiator from other products used in the trade of goods and or services. The role of the trademark is needed as a product identity, quality assurance so it needs to be protected. Toward the passing off well-known trademark that often occurs in Indonesia can weaken the country's economy, therefore it is necessary to take action to overcome this. This study uses a normative legal research method with an approach using laws and regulations as a reference. Friedman's legal system theory is used as an analytical knife to overcome these problems, namely through legal structure, legal substance and legal cultureKeywords: Passing off, Well-known trademark, Friedman's legal system theory